(untitled) (Scientific journal of the Fergana State University, 2024)
In recent years, the view that language learning is not free of mistakes and that mistakes should be understood as a factor indicating positive progress in the language learning process has been widely discussed. Indeed, mistakes show that the language learner is trying to learn something. This article deals with the use of communicative games to correct lexical and grammatical errors that are often made by language learners.